1969
DOI: 10.1136/bmj.1.5643.541
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim-Sulphamethoxazole: Comparative Study in Urinary Infection in Hospital

Abstract: , [541][542][543][544] ummary: Trimethoprim is inhibitory for a wide range of bacteria, and when used in combination with a sulphonamide marked synergy has been reported.In order to test its value in the treatment of urinary infections 154 hospital patients with infections of varying severity and due to a wide range of organisms were treated with combinations of sulphamethoxazole and trimethoprim. Combinations of these substances in two different ratios (2 : 1 and 10: 1) were used in 113 patients, and one week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
1
1

Year Published

1973
1973
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 6 publications
1
31
1
1
Order By: Relevance
“…D avies et al, [1971] showed that cephalexin and ampicillin had a cure rate of about 60°/o in hospital patients with urinary tract infections. The cure rate amongst similar patients treated with co-trimoxazole was 67% [Reeves et al, 1969]. Amongst those six patients in whom treatment failed it was in teresting to note that four had pathological conditions present in their ur ogenital tract, and therefore treatment failure was not unexpected.…”
Section: Discussionmentioning
confidence: 88%
“…D avies et al, [1971] showed that cephalexin and ampicillin had a cure rate of about 60°/o in hospital patients with urinary tract infections. The cure rate amongst similar patients treated with co-trimoxazole was 67% [Reeves et al, 1969]. Amongst those six patients in whom treatment failed it was in teresting to note that four had pathological conditions present in their ur ogenital tract, and therefore treatment failure was not unexpected.…”
Section: Discussionmentioning
confidence: 88%
“…The degree of potentiation of the two components as determined by the agar-diffusion method (2.5 times according to an analysis of the regression lines presented by Dornbusch [9] as well as by Gallien and Schonfeld [11]) is much smaller than that obtained with the agar-dilution test (10-20 times according to various other au thors [4,5,9,11] and our own results). R eeves et al [18] have stated that the therapeutic success could usually be predicted from the result of testing the sensitivity to TMP. We believe that the agar-diffusion test with two discs containing the single components or with only one disc containing TMP alone would be a useful method of sensitivity testing.…”
Section: Discussionmentioning
confidence: 99%
“…With the combination of TMP and SMZ this requirement has not yet been ful filled. Although many papers have been published concerning the clini cal effectiveness of this combination [3,7,13,18], TMP alone has only been investigated a few times [7,14,15,16,19].…”
mentioning
confidence: 99%
“…The urine levels of the drug are very variable, as is usually the case, but are adequate for the eradication of most urinary pathogens. A 75-percent cure rate at the end of a 4-to 6-week follow-up is very encouraging and compares favourably with trials of other agents in similar patients treated with oral antibiotics [3,4].…”
Section: Discussionmentioning
confidence: 50%